Uncovering the spectrum of adult zebrafish neural stem cell cycle regulators - Caron, Aurélien; Trzuskot, Lidia; Lindsey, Benjamin W. (Frontiers in Cell and Developmental Biology, 2022)
Adult neural stem and progenitor cells (aNSPCs) persist lifelong in teleost models in diverse stem cell niches of the brain and spinal cord. Fish maintain developmental stem cell populations throughout life, including both neuro-epithelial cells (NECs) and radial-glial cells (RGCs). Within stem cell domains of the brain, RGCs persist in a cycling or quiescent state, whereas NECs continuously divide. Heterogeneous populations of RGCs also sit adjacent the central canal of the spinal cord, showing infrequent proliferative activity under homeostasis. With the rise of the zebrafish (Danio rerio) model to study adult neurogenesis and neuroregeneration in the central nervous system (CNS), it has become evident that aNSPC proliferation is regulated by a wealth of stimuli that may be coupled with biological function. Growing evidence suggests that aNSPCs are sensitive to environmental cues, social interactions, nutrient availability, and neurotrauma for example, and that distinct stem and progenitor cell populations alter their cell cycle activity accordingly. Such stimuli appear to act as triggers to either turn on normally dormant aNSPCs or modulate constitutive rates of niche-specific cell cycle behaviour. Defining the various forms of stimuli that influence RGC and NEC proliferation, and identifying the molecular regulators responsible, will strengthen our understanding of the connection between aNSPC activity and their biological significance. In this review, we aim to bring together the current state of knowledge on aNSPCs from studies investigating the zebrafish CNS, while highlighting emerging cell cycle regulators and outstanding questions that will help to advance this fascinating field of stem cell biology.